IN VIVO-ANTI-DIABETIC ACTIVITIES OF CRUDE EXTRACTS OF BALINITE AEGYPTICA AND TERMINAIA CATARPA PLANTS - Saidu Garba; MO YAKUBU; SD KINGSLEY (Academy Journal of Science and Engineering)
The phytochemical screening and antidiabetic activities of crude extracts of Balanite aegytica and Terminalia catarpa were investigated and compared with the standard drugs using standard methods. The results of phytochemical screening reveal the presence of alkaloids, flavonoids, phenols, glycosides and Tannins at varying concentrations. The results of antidiabetic test reveal that Balanites aegytica and Terminalia catappa possess moderate to higher activities with Balanites aegytica showing higher activity than the standard drug. Results statistical analysis of the two plants against the standard drugs shows that Balanites aegytica posses significant change of 59% reduction of blood sugar at 50 mg on day 7 and 49% reduction on day 14 for Fasting blood sugar as against the standard drugs Metformin which shows 11% reduction at 50 mg on day 7 and 21% at 100 mg on day 14. The results of toxicity test shows that the two crude extracts and the standard drugs were safe at lower concentrations but unsafe at higher concentration with standard drug having higher toxicity that could cause liver damage at 150 mg. The results of this research therefore showed that Balanites aegytica plant can be used for the treatment of diabetics.